Propuesta de guía de los elementos logísticos relevantes para el proceso de exportación de pitahaya amarilla desde el municipio de La Plata (Huila) al mercado internacional - Dussán Rivera, Paula Andrea (Universidad Antonio Nariño, 2023)
The purpose of this monograph was to design a proposal to guide the relevant logistic elements for the export process of yellow pitahaya from the municipality of La Plata (Huila) to the international market with the objective of fulfilling the purpose proposed by the producers of the municipality according to their business vision. The monograph is developed under the format of a descriptive study with a mixed approach (quantitative-qualitative) whose information was obtained through primary and secondary sources. The project was structured through three central objectives that guided the research, on the one hand, the storage structure for the export process, on the other hand, the packing and packaging model for the export of yellow pitahaya and finally the factors required to initiate an export process. Likewise, the study was developed under an approach of international economics and international trade where the main objective was to contribute to the development of the department of Huila through the fruit sector and the consequent increase in exports.